Probelamatika Minuta Akta Notaris Yang Diberhetikan Secara Tidak Hormat - Angelina Marsella (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2024)
A notary is a public official who has the authority to make an authentic deed. The authentic deed itself can is said to be authentic if it is made in accordance with the provisions Laws and made by or before officials general who has authority. This authentic deed can be is said to be the most important deed because it is a tool the strongest and fullest written evidence makes a real contribution for resolving cases. Notaries who can make deeds this authenticator is a Notary who is authorized by law determined to still be authorized, namely a current Notary practicing and not on leave, temporarily dismissed, honorably dismissed, or disrespectfully dismissed. But that's the problem is how the client's good impact on the validity of the minutes deed that has not been signed by a Notary who has dishonorably discharged, and what should be done carried out by a Substitute Notary regarding the minutes of the deed and the copies that have been issued? Keywords: Notary, Authenthic Deed, Minutes of Deed.